Can Plant-Derived Anti-Inflammatory Compounds “Replace” Indomethacin in NSAID Therapy? Advances in Drug Delivery Systems of Indomethacin and Off-Label Medical Applications - Petya Georgieva; Petya Peneva; Yana Gvozdeva (Applied Biosciences, 2026)
Non-steroidal anti-inflammatory drugs (NSAIDs) are widely used for the management of inflammatory disorders, pain, and fever due to their significant anti-inflammatory and antipyretic properties. However, their long-term use is often associated with multiple adverse effects, including gastric erosion, hemorrhage, and perforation, as well as cardiovascular, hepatic, and renal complications. Indomethacin is a potent NSAID commonly used in the treatment of pain and rheumatoid arthritis. Its poor water solubility, Biopharmaceutics Classification System (BCS) Class II, results in low aqueous solubility and high membrane permeability, and conventional dosage forms often fail to overcome pharmacokinetic limitations and gastrointestinal irritation. To address these drawbacks, alternative indomethacin-loaded drug delivery systems have been developed, which enable controlled release, enhanced solubility, and targeted delivery for improving therapeutic efficacy and safety profile. Nature provides a diverse reservoir of bioactive compounds with significant anti-inflammatory potential, making them promising alternatives or complementary agents to indomethacin. Representative examples include the alkaloids piperine and berberine; the flavonoids oleocanthal and apigenin; and the terpenoids thymoquinone, kahweol, and cafestol; as well as anthraquinones and iridoids. This review summarizes the current evidence on plant-derived anti-inflammatory compounds that may “replace” or act synergistically with indomethacin. In addition, we discuss the pharmacological properties of indomethacin and recent advances in drug delivery systems designed to improve its topical and systemic therapeutic applications.